630 nm nightglow observations from 17 degree N latitude - Mukherjee, G. K.; Carlo, L.; Mahajan, S.H. (My University, 2000)
Regular measurements of [OI] 630 nm nightglow have been carried out at Kolhapur (16.8◦N, 74.2◦E, dip lat 10.6◦N) in India with the help of tilting filter photometers during clear moonless nights. Several characteristic nightglow data sets are presented in the report for geomagnetically quiet and disturbed nights. A comparison has been made between the simultaneous nightglow and the ionospheric parameters of virtual F-layer height and critical frequency of the F-layer at Ahmedabad (23.02◦N, 72.6◦E). In general, a good correlation (c.c. = 0.8 to 0.9) is found between the measured airglow emission and F-region peak electron densities during quiet periods but for intense magnetic disturbances the airglow fluctuations are mainly controlled by sharp changes in height variations of the h F layer. The period of airglow variation generally corresponds to periods of F-region height variation during magnetic disturbances. Using a long series of data between December 1989 and April 1996, the mean seasonal nocturnal variations of 630 nm emission have been compared during high and low solar activity periods.
Keywords: Magnetic disturbance; F-layer; Electron density; Solar activity